VILLAGE DEMOCRATIZATION IN THE NEW ORDER ERA: The Shifting Value and Orientation of the Village Leaders and the Faded Motivation among the People to become a Head of Village (a Case in the Head of Village Election at Sangiang Banjar Subdistrict Majalengka Regency) - Saefulrahman, Iyep -; Suwaryo, Utang -; -, Rudiana - (Advances in Social Sciences Research Journal, 2017)
Abstract Sangiang Village cannot be separated from the will of the state considering its position as law community unit in Indonesia. The direction of village governance and democracy should be able to conform to a centralized policy of the state and its uniformity. As a result, the village no longer has eligible to control and manage interests of village and its denizens; likewise, there have been a shift of sanctity of village chief and a lack of denizens’ motivation to obtain its position. This research is aimed at gaining a deep analysis of the democratization in Desa Sangiang during the New Order era, particularly on the execution of Village Government Law Number 5/1979 (UU No.5 Tahun 1979) including its technical regulations. Qualitative approach adopted is to answer the aim of research through documentation and in-depth interview. This research seeks to show that during Village Chief election in Desa Sangiang there is an implementation of liberal tradition that leads to a formal democracy. It occured due to the state perspective in internalising the democracy values tend to be more procedural than substantive that have formed the conformity of village to pay off its duties before the state. Subsequently, the state policy in adjusting the power of village chief has bureaucratically shaped the shift of values and characters of village chief itself. It also become one of the reason why the denizens’ motivation to be a village chief in Desa Sangiang have decreased. These findings suggests it is proper that Government has to learn to what occurred in Desa Sangiang during the New Order era, in order to build a meaningful democracy in village through emphasizes the embodiment of substantive democracy than the procedural democracy. Keywords: democratization, village, village chief